USING MODULAR TECHNOLOGIES IN CREATING ELECTRONIC COURSE (World Bulletin of Social Sciences, 2022)
The issues of the development of electronic training courses of a new generation, built on a modular principle, are considered. Such construction of educational material makes it possible to improve the quality of students' education, increase the amount of material studied, it is easier to organize distance learning and an individual approach to the student